2016
DOI: 10.1186/s12885-016-2071-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of irinotecan (SN-38) resistant human breast cancer cell lines

Abstract: BackgroundStudies in taxane and/or anthracycline refractory metastatic breast cancer (mBC) patients have shown approximately 30 % response rates to irinotecan. Hence, a significant number of patients will experience irinotecan-induced side effects without obtaining any benefit. The aim of this study was to lay the groundwork for development of predictive biomarkers for irinotecan treatment in BC.MethodsWe established BC cell lines with acquired or de novo resistance to SN-38, by exposing the human BC cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 47 publications
7
32
0
Order By: Relevance
“…However, the expression level was in low intensity meaning that ABCG2 existed in low copy numbers on the cell surfaces (Figure S1). Since OVASC‐1 cells express MDR1 in high copy numbers but ABCG2 in low copy numbers, our data related to the sensitivity of OVASC‐1 to SN‐38 at nanomolar (nmol/L) concentrations appears to rule out MDR1 as a prominent mediator of SN‐38 resistance, and agree with the more recent studies reported in 2016 22, 23. This interesting observation highlights the importance of personalized therapy, in which an IP sample could be taken from each patient and analyzed for ABCG2 expression.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…However, the expression level was in low intensity meaning that ABCG2 existed in low copy numbers on the cell surfaces (Figure S1). Since OVASC‐1 cells express MDR1 in high copy numbers but ABCG2 in low copy numbers, our data related to the sensitivity of OVASC‐1 to SN‐38 at nanomolar (nmol/L) concentrations appears to rule out MDR1 as a prominent mediator of SN‐38 resistance, and agree with the more recent studies reported in 2016 22, 23. This interesting observation highlights the importance of personalized therapy, in which an IP sample could be taken from each patient and analyzed for ABCG2 expression.…”
Section: Resultssupporting
confidence: 92%
“…The sensitivity of the OVASC‐1 cells to SN‐38 was also interesting. Some older studies have indicated that SN‐38 is a substrate for both the MDR1 and the ABCG2 drug efflux pumps,21 whereas recent evidence suggests that the ABCG2 pump is a key mediator of SN‐38 resistance 22, 23. To shed more light on this ambiguity, we measured the expression levels of the ABCG2 transporter in OVASC‐1 cells.…”
Section: Resultsmentioning
confidence: 93%
“…When cultured in vitro, SN-38-resistant sublines of MCF-7 or MDA-MB-231 had longer doubling times than their parental cells (43). Thus, it is not surprising that NCI-N87-S120 xenografts grew significantly slower in the mice than NCI-N87, which is consistent with the notion that drug-resistant tumor sublines selected in vitro frequently manifest less aggressive properties than their drugsensitive parental cell lines (49).…”
Section: Improved Efficacy Of Immu-132 When Combined With Yho-13351 Isupporting
confidence: 75%
“…Cross-resistance of these sublines to doxorubicin varied somewhat, with the resistance ratio (IC 50 in resistant subline divided by IC 50 in the parental cell) being less than 1.3 for the sublines of PC-6 (17), 2.5 for the sublines of HeLa (45), and about 7.0 for the subline of H23 (44). Whereas cross-resistance to doxorubicin was not determined for the SN-38-resistant sublines derived from MCF-7 (42,43) or MDA-MB-231 (43), these sublines remained sensitive to vincristine (42), cisplatin (42,43), and docetaxel (43). Although we and others have established ABCG2 as a key player in reducing SN-38 sensitivity of various SN-38-resistant cancer sublines, the potential involvement of DNA topoisomerase I (Top1), to which SN-38 specifically binds and acts as an inhibitor, in the SN-38 resistance mechanism of such cancer cells, is less defined and remains a focus of continuous research, with the current knowledge pointing to Top1 mutation (46,47) and degradation (48) as the two main roles of Top1 underlying the molecular mechanism of resistance to camptothecin in general and SN-38 in particular.…”
Section: Improved Efficacy Of Immu-132 When Combined With Yho-13351 Imentioning
confidence: 99%
See 1 more Smart Citation